2020
DOI: 10.1038/s41523-020-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of adjuvant radiation and chemotherapy on peripheral blood epigenetic age in early stage breast cancer patients

Abstract: Survival has increased in early stage breast cancer (BC), and the late effects of treatment persist for decades. Molecular mechanisms underlying the acceleration of age-related diseases after chemotherapy and radiotherapy are poorly understood. We examined epigenetic changes in peripheral whole blood cells in early stage BC patients undergoing surgery followed by adjuvant radiotherapy, or surgery followed by adjuvant chemotherapy and radiotherapy. DNA methylation experiments were performed on whole blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 42 publications
8
42
3
Order By: Relevance
“…In addition, similar effects of chemotherapy and irradiation on telomere length have been reported ( 14-18 ). Also, measurement of additional biomarkers of aging that capture various molecular mechanisms of aging, such as an increase in inflammation (the measurement of the senescence-associated secretory phenotype) ( 10 ), epigenetic changes ( 19 , 20 ) (DNA methylation panels), and changes in metabolism, may deepen our understanding of processes affected by chemotherapy. Taken together, our results suggest that the choice of chemotherapy regimen, as well as the baseline “molecular age” of the patient, are important factors that determine the pro-aging capacity of chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, similar effects of chemotherapy and irradiation on telomere length have been reported ( 14-18 ). Also, measurement of additional biomarkers of aging that capture various molecular mechanisms of aging, such as an increase in inflammation (the measurement of the senescence-associated secretory phenotype) ( 10 ), epigenetic changes ( 19 , 20 ) (DNA methylation panels), and changes in metabolism, may deepen our understanding of processes affected by chemotherapy. Taken together, our results suggest that the choice of chemotherapy regimen, as well as the baseline “molecular age” of the patient, are important factors that determine the pro-aging capacity of chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Finding biomarkers of aging that capture changes over the entire lifespan and reflect the clinical aspects of aging is a rich and expanding area of research ( 12 , 13 ). Potential biomarkers include inflammatory markers, telomere length ( 14-18 ), sarcopenia, DNA methylation ( 19 , 20 ), and maximal oxygen consumption (vO 2 max) ( 21 ). Expression of p16 INK4a , a biomarker of senescence, is considered a fundamental and dynamic measurement of molecular aging with a 10-fold increase in gene expression between ages 20 and 80 years ( 22 ).…”
mentioning
confidence: 99%
“…Not only has epigenetic clock been used to predict cancer risk, but also it has been tested in cancer survivors. For example, a recent study of 72 women with early-stage breast cancer (37 received radiation therapy alone and 35 received chemotherapy and radiotherapy) reported a statistically significantly increase in EEAA ( p = 0.0021), PEAA ( p = 0.015), and GEAA ( p = 3.2 × 10 −6 ) from pre-treatment to post-treatment, but not in IEAA [ 86 ]. Another study tested the Weidner’s clock in 19 patients with HCT [ 13 ].…”
Section: Measurements Of Accelerated Aging In Cancer Survivorsmentioning
confidence: 99%
“…When peripheral CD8 + T lymphocytes were assessed in metastatic breast cancer patients during the post-salvage taxane chemotherapy follow-up, it was found that CD8 + CD28 − populations were increased in breast cancer patients compared to the control cohort [ 23 ]. In another longitudinal study, radiotherapy and chemotherapy in early-stage breast cancer patients increased senescent cytotoxic T lymphocytes [ 59 ]. Shortened telomere length was observed in peripheral blood mononuclear cells in non-Hodgkin’s lymphoma patients undergoing chemotherapy [ 60 ].…”
Section: Mechanisms Of T Cell Senescence Inductionmentioning
confidence: 99%